Synthesis of the cyanobacterial halometabolite Chlorosphaerolactylate B and demonstration of its antimicrobial effect in vitro and in vivo - Jensen, Nikoline; Jensen, Henrik Elvang; Aalbaek, Bent; Blirup-Plum, Sophie Amalie; Soto, Sara M.; Cepas, Virginio; López, Yuly; Gabasa, Yaiza; Gutiérrez-del-Río, Ignacio; Villar, Claudio J.; Lombó, Felipe; Iglesias, María José; et al. (Frontiers in Microbiology, 2022)
Chlorosphaerolactylate B, a newly discovered antimicrobial halometabolite from the cyanobacterium Sphaerospermopsis sp. LEGE 00249 has been synthesized in three steps by using 12-bromododecanoic acid as starting material. A total of 0.5 g was produced for in vitro and in vivo antimicrobial efficacy testing. In vitro, the minimal inhibitory concentration (MIC) was estimated to be 256 mg/L for Staphylococcus aureus, while the minimal biofilm inhibitory concentration (MBIC) was estimated to be 74 mg/L. The in vivo study utilized a porcine model of implant-associated osteomyelitis. In total, 12 female pigs were allocated into 3 groups based on inoculum (n = 4 in each group). An implant cavity (IC) was drilled in the right tibia and followed by inoculation and insertion of a steel implant. All pigs were inoculated with 10 µL containing either: 11.79 mg synthetic Chlorosphaerolactylate B + 104 CFU of S. aureus (Group A), 104 CFU of S. aureus (Group B), or pure saline (Group C), respectively. Pigs were euthanized five days after inoculation. All Group B animals showed macroscopic and microscopic signs of bone infection and both tissue and implant harbored S. aureus bacteria (mean CFU on implants = 1.9x105). In contrast, S. aureus could not be isolated from animals inoculated with saline. In Group A, two animals had a low number of S. aureus (CFU = 6.7x101 and 3.8x101, respectively) on the implants, otherwise all Group A animals were similar to Group C animals. In conclusion, synthetic Chlorosphaerolactylate B holds potential to be a novel antimicrobial and antibiofilm compound.